About some paradoxes of modern mass communication. (Eurasian Journal of Philology Science and Education, 2015)
The article is devoted description of some paradoxical features of modern mass communication. Growth of role of addressee is marked at presence of wide possibilities for an author public self-expression, returning to the archaicforms of communication in the conditions of intensive development of technical means, lowering of quality of perception and understanding of information at the permanent increase of its volume. It is necessary principal reason, defiant these paradoxes, to count the unbalanced co-operation of author and addressee in the field of mass communication.
Keywords: mass communication; information; participants of communication; mass media